HOW DOES THE STORE (MALL) ENVIRONMENT AND MONEY AVAILABILITY AFFECT CONSUMER IMPULSE BUYING BEHAVIOR AT SURABAYA CITY OF TOMORROW SHOPPING CENTER? - Hendra, Hendra; Kaihatu, Thomas Stefanus (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to determine the effect of store (mall) environment and money availability on consumer impulse buying in the City of Tomorrow (Cito) Surabaya. This study uses a quantitative approach whose data is obtained from the results of questionnaires. The sample in this study were 389 respondents taken based on purposive sampling technique which was included in non-probability sampling techniques. The results of this study indicate that the store (mall) environment has no effect on impulse buying. Meanwhile, money availability has a positive and significant effect on consumer impulse buying in the City of Tomorrow (Cito) Surabaya.